2016
DOI: 10.1292/jvms.14-0637
|View full text |Cite
|
Sign up to set email alerts
|

Development of ovarian diseases in dairy cows with a history of fatty liver, and their prognosis

Abstract: In the present report, the incidence and prognosis of ovarian diseases were evaluated in correlation to the grades of the fatty livers (FL). 233 animals were diagnosed with a FL, based on fat deposition of >10% into the hepatic parenchyma obtained from liver biopsy, and were eventually cured of the FL. These 233 animals were classified into mild group (n=99: hepatic fat deposition rates ranging from 10 to <30%), moderate group (n=56: hepatic fat deposition rates ranging from 30 to <60%) and severe group (n=78:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
3
0
4
Order By: Relevance
“…The study conducted by Janovick et al (2011) where they fed 80% (low), 100% (restricted) and 150% (high) of NRC requirements during pre-partum period found that feeding above NRC requirements resulted into increased mobilization of fat reserves and incidence of metabolic disorders as compared to restricted and under low fed cows during pre-partum period. Tanemura et al (2016) reported that with the increase in fat deposition rate (60% or higher) on liver increases the death or culling rates (69.7 %) and also increased the ovarian disease recurrence rates (84.9%). This further explains why in our study the low pregnancy rate and higher mortality observed in treatment High.…”
Section: Post-partum Oestrus Interval and Services Permentioning
confidence: 99%
“…The study conducted by Janovick et al (2011) where they fed 80% (low), 100% (restricted) and 150% (high) of NRC requirements during pre-partum period found that feeding above NRC requirements resulted into increased mobilization of fat reserves and incidence of metabolic disorders as compared to restricted and under low fed cows during pre-partum period. Tanemura et al (2016) reported that with the increase in fat deposition rate (60% or higher) on liver increases the death or culling rates (69.7 %) and also increased the ovarian disease recurrence rates (84.9%). This further explains why in our study the low pregnancy rate and higher mortality observed in treatment High.…”
Section: Post-partum Oestrus Interval and Services Permentioning
confidence: 99%
“…Prevalência de cisto, classificação ovariana e distribuição dos cistos entre ovário direito, ovário esquerdo e cistos bilaterais*. O presente estudo, balizou-se também, na presença de estruturas ovarianas ≥ 20 mm, para o diagnóstico dos cistos e ainda distribui os cistos conforme sua localização, no ovário direito foram identificados 59,6% (n = 131), no ovário esquerdo 33,6% (n = 131) e a disposição bilateral em 6,8% (n = 131), resultados estatisticamente significativos, de acordo com a Tabela 2, que está em consonância com outros pesquisadores, cujos trabalhos foram pautados na distribuição dos cistos foliculares em vacas de leite (ZULU & PENNY 1998, MADUREIRA et al 2002, HATLER et al 2003, PATTON et al 2007 (GAEBLER et al 2015, TANEMURA et al 2016. Já ZULU & PENNY (1998) descreveram a ocorrência de cistos ovarianos em vacas de leite de 20 a 150 dias após o parto.…”
Section: Prevalência De Cisto Ovariano E Classificação Ovariana De Vaunclassified
“…Quanto à disposição dos cistos ovarianos conforme o Escore de condição corporal dos animais (ECC). O ECC é uma medida visual, prática e de baixo custo (BARTOLOME et al 2005), usada para monitorar o estado nutricional e o desempenho reprodutivo de vacas de leite em várias regiões do mundo, pois é determinante na reconcepção e na produtividade geral do rebanho (FERNANDES et al 2005, TANEMURA et al 2016.…”
Section: Ocorrência De Cistos Ovarianos De Acordo Com O Escore De Conunclassified
See 1 more Smart Citation
“…Fatty liver is the major cause of periparturient diseases [ 4 , 29 , 30 ] and reproductive disorders [ 5 , 20 , 25 ]. We have previously demonstrated that dairy cows with moderate or severe fatty liver after parturition tend to develop various secondary diseases, including follicular cysts, and many become disused and are culled within a year [ 26 ]. It has been reported that approximately 23% of the first follicular waves after parturition [ 2 , 3 ] or in the early postpartum period [ 21 ] become follicular cysts in dairy cows.…”
mentioning
confidence: 99%